2012
DOI: 10.1002/cne.22745
|View full text |Cite
|
Sign up to set email alerts
|

Toward a single‐cell‐based analysis of neuropeptide expression in Periplaneta americana antennal lobe neurons

Abstract: A multitude of potential neurotransmitters and neuromodulators, including peptides, have been detected in the antennal lobe (AL), the first synaptic relay of the central olfactory pathway in the insect brain. However, the functional role of neuropeptides in this system has yet to be revealed. An important prerequisite to understanding the role of neuropeptides is to match the functionally different cell types in the AL with their peptide profiles by using electrophysiological recordings combined with immunocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 82 publications
7
67
0
Order By: Relevance
“…Additional LN types do exist that are neither GABAergic nor cholinergic, and the chemical identity of these subtypes remains to be uncovered. Previous immunocytochemical and mass spectrometric studies have shown that AL neurons can contain a variety of potential neurotransmitters and neuromodulators (Loesel and Homberg, ; Nässel and Winther, ; for reviews see Homberg, ; Homberg and Müller, ; Neupert et al, ). Overlapping expression patterns also suggested that classical transmitters might colocalize with potential neuromodulators such as biogenic amines (Dacks et al, , , ; Ignell, ; Sachse et al, ) and peptides (Berg et al, ; Nässel and Homberg, ; Nässel and Winther, ; Utz et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional LN types do exist that are neither GABAergic nor cholinergic, and the chemical identity of these subtypes remains to be uncovered. Previous immunocytochemical and mass spectrometric studies have shown that AL neurons can contain a variety of potential neurotransmitters and neuromodulators (Loesel and Homberg, ; Nässel and Winther, ; for reviews see Homberg, ; Homberg and Müller, ; Neupert et al, ). Overlapping expression patterns also suggested that classical transmitters might colocalize with potential neuromodulators such as biogenic amines (Dacks et al, , , ; Ignell, ; Sachse et al, ) and peptides (Berg et al, ; Nässel and Homberg, ; Nässel and Winther, ; Utz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To understand precisely the physiological role of potential transmitters and neuromodulators in the AL, it is essential to match the different AL neuron types with their biochemical profiles by combining electrophysiological recordings with immunohistochemical studies and/or single‐cell mass spectrometry (Neupert et al, ). The marked physiological differences between LN types imply direct consequences for their computational capacity and synaptic output kinetics, and thus their functional role in the olfactory circuit.…”
Section: Discussionmentioning
confidence: 99%
“…The double‐label experiments allowed for discrimination of branches of individual SIFamide‐ir neurons among the meshwork of intermingled neurites originating from the different cell groups. With matrix‐assisted laser desorption/ionization–time of flight (MALDI‐TOF) mass spectrometry (MS), it was shown that the amino acid sequences of SIFamides from R. maderae and T. petiveriana are identical to SIFamide of P. americana , which confirmed the conserved nature of this neuropeptide in insects (Neupert et al, ), whereas behavioral data from R. maderae demonstrated a function as an input factor into the circadian clockwork.…”
Section: Sifamide Isoforms Found In Arthropodsmentioning
confidence: 91%
“…Detecting multiple predicted peptides by their molecular mass often is sufficient to assign peptides to a certain prohormone, in the same way as the peptide mass fingerprint method is widely used in proteomics for protein identification. This approach allows matching of the individual cell peptide profiles to electrophysiological activity [72], localization of molecular probes [73], or both [74, 75]. A unique two-step strategy hyphenates MS to targeted chemical analysis of immunocytochemical-selected peptidergic neurons containing selected biomarkers of interest [76].…”
Section: Choosing Your Peptidomics Modus Operandi: a Guide On Methodomentioning
confidence: 99%